2010
DOI: 10.1130/b26566.1
|View full text |Cite
|
Sign up to set email alerts
|

Structural evolution of the Neogene Gar Basin, western Tibet: Implications for releasing bend development and drainage patterns

Abstract: We investigated the interaction among basin-bounding faults, basin fi ll, and geomorphic features of the southern Gar Basin, one of only two known releasing double-bend basins along the Karakoram fault, to better understand their structural evolution and role in basin development. The southern Gar Basin is bounded by an ~44-km-long, N20°Wstriking central fault segment fl anked by two N40°W-striking segments that parallel the regional strike of the Karakoram fault system. The central fault segment is composed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 63 publications
(89 reference statements)
1
13
0
Order By: Relevance
“…The new Zircon U-Pb ages reported in this study confirm that the Proterozoic to Ordovician rocks in the footwall of the Ayi Shan detachment are part of the Ayilari Ranges (Xizang BGMR 2005;Sanchez et al 2010;Zhang et al 2011;Wang et al 2013). Previous research has shown that the Ayilari Range consisted mainly of three episodes of granites at ∼60 Ma, 45-50 Ma, and 32-25 Ma (Lacassin et al 2004;Valli et al 2007Valli et al , 2008Wang et al 2009Wang et al , 2011.…”
Section: Chronological Constraint On Activity Of Kkfsupporting
confidence: 80%
See 1 more Smart Citation
“…The new Zircon U-Pb ages reported in this study confirm that the Proterozoic to Ordovician rocks in the footwall of the Ayi Shan detachment are part of the Ayilari Ranges (Xizang BGMR 2005;Sanchez et al 2010;Zhang et al 2011;Wang et al 2013). Previous research has shown that the Ayilari Range consisted mainly of three episodes of granites at ∼60 Ma, 45-50 Ma, and 32-25 Ma (Lacassin et al 2004;Valli et al 2007Valli et al , 2008Wang et al 2009Wang et al , 2011.…”
Section: Chronological Constraint On Activity Of Kkfsupporting
confidence: 80%
“…Notes: GCT, Great Counter thrust; KKF, Karakoram Fault System; MBT, Main Boundary Thrust; MCT, Main Central Thrust; MFT, Main Frontal Thrust; STD, South Tibetan Detachment. Map is compiled from Murphy et al (2000), Xizang BGMR (2005), Sanchez et al (2010), and Wang et al (2011). fault system, with lenses of serpentinized mafic rocks hundreds of metres long and ultramafic rocks that crop out locally along the fault zone, which defines the surface trace of the Indus-Yalu suture zone. The strata involved in the hanging wall of the GCT are mainly of the PalaeozoicMesozoic Tethyan sedimentary sequence, and mélange from the Indus-Yalu suture (Xizang BGMR 2005).…”
Section: Geological Settingmentioning
confidence: 99%
“…The dome extends northeast to the Ayi Shan that is bound by the Karakoram fault system (Valli et al. , 2007; Sanchez et al. , 2010) (Fig.…”
Section: Geological Settingmentioning
confidence: 99%
“…Metamorphic isograds are from this study and Chambers et al (2009). Mineral abbreviations after Kretz (1983). dome extends northeast to the Ayi Shan that is bound by the Karakoram fault system (Valli et al, 2007;Sanchez et al, 2010) (Fig. 1).…”
Section: Geological Settingmentioning
confidence: 99%
“…However, Valli et al (2007) suggest it was continuously active since the Early Miocene, based on U-Pb zircon ages and petrofabric analyses of rocks exposed on its south side (footwall). The Karakoram fault is presently active as it offsets Quaternary surfi cial deposits (Armijo et al, 1989;Chevelier et al, 2005;Brown et al, 2002;Murphy and Burgess, 2006;Sanchez et al, 2010).…”
Section: Karakoram Fault Systemmentioning
confidence: 99%